“GLORY TO ARTISTIC SKILL”: EKPHRASIS OF FINE ARTS IN P. ZAHREBELNYI`S NOVEL “WONDER” - Nataliia L. Bilyk. (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2023)
In the retrospective panorama of comparative studies experience, attention to ekphrasis seems to be more and more intense. The multifaceted phenomenon of ekphrasis does not lose its relevance over time. Vivid ekphrastic features are observed, in particular, in the epic novel “Wonder” written by Pavlo Zahrebelnyi, a prominent figure of Ukrainian literature. The purpose of the investigation is to select the fine arts ekphrasis features in the novel by Pavlo Zahrebelnyi, as well as to highlight the formal and semantic dimensions and the overall semantic configuration of the expressed poetics. The study is based on the methods of cultural-semiotic and structural-semantic analysis in combination with descriptive and comparative-typological approaches. In the visual material of Zahrebelnyi`s novel “Wonder”, the poetics of multidirectional multidimensional ekphrasis is observed, in which, according to the criterion of the image carrier, the actualization of several types of visual art is distinguished, in particular decorative and (related to it) monumental one, and their types: artistic carving, fresco painting and mosaic. In the descriptions there is a gradual development with a noticeable transgression of the content of the represented works and, therefore, the content of the ekphrasis itself. In the structure of the work their selected defining features are obviously related to one of the key organizational phenomena, one of the central symbols inherent in the “Wonder”: ekphrases in its general architecture are connected by integral elements belonging to the sphere of the internal form. Such connecting elements are cross-cutting for ekphrasis, key for the novel, tangential images-symbols of the creator, his skill and art in general, which causes the integration of expressed ekphrases into a single composite complex. In it the meaningfulness of the ekphrasis in the poetic field of the master turns out to be equal to his artistic destiny, through the fresco-like combination of the described achievements features emerge the lines of inspired children`s creative maturation, youthful strengthening and ultimately artistic work are drawn, in which the apogee of the artist’s talent, in all its polychromy, is finally reached: in essence, in purpose and meaning. In its turn, in the discreteness of the descriptions indirectly reveals the dynamics of its evolution, the amplitude of which from the seed of inspired abilities reaches the exuberance of an all-powerful philanthropic mastery, sensual and sensitive, insightful, frank, caring, which overcomes existential reflections in its longing for the good, bringing creativity closer to life-affirming thought. And all these phases have one common quality: humanity is imprinted in each of them. With the isolated potential of ekphrasis, the poetics of the novel rises to the horizons of the creativity existence idea and achievements of an artistic genius for “creating a temple”, in particular in the human soul, and from this semantic palette emerges a kind of “glorification of artistic skill” not only by the perfection of its magnificent creations, but also primarily by imprinted in them love for life and the world, singing of beauty, equivalent to the unity of goodness and humanity. In this way, the highlighted experience of ekphrasis obviously strengthens the expression of humanity in the axiological dimensions of civilizational assets in Pavlo Zahrebelnyi`s novel “Wonder”.